[OSSO]‐Type Fe(III) Metallate as Single‐Component Catalyst for the CO2 Cycloaddition to Epoxides. Issue 2 (30th October 2018) - Della Monica, Francesco; Buonerba, Antonio; Paradiso, Veronica; Milione, Stefano; Grassi, Alfonso; Capacchione, Carmine
Abstract: A new [OSSO]‐Fe(III) metallate complex was prepared and characterized. We demonstrated that such metallate is the real catalytic active species for the cycloaddition of CO2 to the epoxides, formed from the in situ reaction of the related [OSSO]‐Fe(III) neutral complexes and tetrabutylammonium bromide. The metallate complex was used as a single component catalyst for the formation of cyclic organic carbonates from ten epoxides and CO2 at 1 bar pressure with good activity. Abstract :